The Role of Financial Accounting in Enhancing The Corporate Financial Performance of Small and Medium Enterprises - Jaafar Ali Alqudhayeb , Nael (South Asian Journal of Social Sciences and Humanities, 2025)
This research aims to examine the relationship between financial accounting and the corporate financial performance (CFP) of Malaysian small and medium-sized enterprises (SMEs). The study employed a sample of 120 SMEs spanning the years 2018 to 2024, utilizing secondary data from annual reports and database by using OLS to test the regression analysis. The study found a positive and strong relationship between financial accounting and CFP. The research highlights the essential role that transparent financial accounting and accurate plays in supporting administrative decision-making and financial within firms, contributing to enhanced performance. It also proved that implementing current accounting standards improves the consistency of financial information, which enhances stakeholder and investor confidence and positively influence financial sustainability and growth. The research recommends that firms adhere to financial accounting by accounting standards, improve internal control systems for the financial information, and support the effectiveness of accounting personnel to guarantee transparent financial performance and sustainable.